PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Marhamah, Marhamah; Susanto, Edy (JAB (Jurnal Akuntansi & Bisnis), 2021)
Investors in investing their funds expect returns from high share prices, which reflect good company value which means prosperity for shareholders. The purpose of this study is the disclosure of Corporate Social Responsibility (CSR) and Good Corporate Governance Mechanisms on Company Value in mining sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The population in this study are manufacturing companies in the mining sector listed on the Indonesia Stock Exchange (IDX), totaling 42 companies. The sample in this study used the purposive sampling method, which obtained a sample of 13 companies. The variables in this study are Corporate Social Responsibility, Good Corporate Governance mechanism (which is proxied by the Audit Committee, Institutional Ownership, and Managerial Ownership), and Company Value. Methods of data collection using documentation. The method of analysis used multiple linear regression. Based on the results of data analysis, it was concluded that Corporate Social Responsibility and GCG Mechanism with Managerial Ownership Proxy had a significant effect on Firm Value, GCG Mechanism with Audit Committee Proxy and Institutional Ownership had no significant effect on Firm Value.Â Keywords : Corporate Social Responsibility, Good Corporate Governance mechanism, Audit Committee, Institutional Ownership, and Managerial Ownership